Product Rule of Exponents :
When multiplying exponential expressions that have the same base, add the exponents.
Simplify each of the following.
Example 1 :
a ⋅ a2 ⋅ a3
Solution :
Using product rule am × an = am+n
= a ⋅ a2 ⋅ a3
= a1+2 ⋅ a3
= a3 ⋅ a3
= a3+3
= a6
Example 2 :
(2a2b)(4ab2)
Solution :
= (2a2b)(4ab2)
Multiply the coefficients,
= (2 × 4) (a2b) (ab2)
= 8(a2b) (ab2)
Combining like terms,
= 8(a2 ⋅ a) (b ⋅ b2)
By am × an = am+n, we get
= 8(a2+1) (b1+2)
= 8a3b3
Example 3 :
(6x2)(-3x5)
Solution :
= (6x2)(-3x5)
Multiply the coefficients,
= (6 × (-3)) (x2) (x5)
By am × an = am+n, we get
= -18(x2+5)
= -18x7
Example 4 :
b3 ⋅ b4 ⋅ b7⋅ b
Solution :
= b3 ⋅ b4 ⋅ b7⋅ b
= b3+4 ⋅ b7+1
= b7 ⋅ b8
= b7+8
= b15
Example 5 :
(3x3) (3x4) (-3x2)
Solution :
= (3x3) (3x4) (-3x2)
Multiply the coefficients,
= (3 × 3 × 3) (x3) (x4) (x2)
= 27 (x3+4) ⋅ (x2)
= 27 (x7 ⋅ x2)
= 27x7+2
= 27x9
Use the product rule to rewrite each expression as a single exponent.
Example 6 :
(-5)-10 ⋅ (-5)15
Solution :
= (-5)-10 ⋅ (-5)15
= (-5)-10+15
= (-5)5
= -3125
Example 7 :
Solution :
Example 8 :
(1.4)-12 ⋅ (1.4)5
Solution :
= (1.4)-12 ⋅ (1.4)5
= (1.4)-12+5
= (1.4)-7
= 0.09486
Example 9 :
Solution :
Example 10 :
(-13)0 ⋅ (-13)-19
Solution :
= (-13)0 ⋅ (-13)-19
= (-13)0-19
= (-13)-19
= -6.84013
Example 11 :
8-14 ⋅ 84
Solution :
= 8-14 ⋅ 84
= 8-14+4
= 8-10
= 9.313
Find the value of x :
Example 12 :
10x ⋅ 10-9 = 1011
Solution :
10x ⋅ 10-9 = 1011
10x-9 = 1011
Since bases are the same, equate the powers.
x - 9 = 11
x = 11 + 9
x = 20
Example 13 :
Solution :
Example 14 :
(-2.9)-13 ⋅ (-2.9)x = (-2.9)-5
Solution :
(-2.9)-13 ⋅ (-2.9)x = (-2.9)-5
(-2.9)-13+x = (-2.9)-5
Since bases are the same, equate the powers.
-13 + x = -5
x = -5 + 13
x = 8
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM